(untitled) (Economic and Political Thought, 2015)
The article presents the basics of economic analysis of the efficiency of hospitals. In the first part, the concept of efficiency is defined on the basis of Pareto’s legacy. Because efficiency can be measured in several ways, the article presents the approach to the economic efficiency of production, which is the product of technical and allocative efficiency, from the perspective of costs, revenues and profits. The second section describes the two main methods for estimating efficiency, namely the method of DEA drawn from linear programming and the econometric method of the SFA representing stochastic and parametric approach. Attention is focused on the problems of determining the efficiency of hospitals and the healthcare system in the following four points. The first issue is whether hospitals achieve economic efficiency understood as a product of technical and allocative efficiency. The second issue, although connected with allocative efficiency, is treated as a separate one because of its significance. It concerns checking whether hospitals are overcapitalized. The third issue refers to the impact of the costs incurred by hospitals on the degree of their specialization. The last issue concerns the impact of the number of hospitals on costs incurred by hospitals and the healthcare system.